The domino effect of teacher cognitive presence triggering events and resolution on student’s grit - Marcu, Radiana; Rad, Dana (Technium Social Sciences Journal, 2024)
The aim of this current study is to assess the essential role of teacher cognitive presence within the context of the community of inquiry framework in relation to enhancing students’ academic perseverance, more specifically this type of presence influences the most students’ academic perseverance. In order to test this hypothesis, an online questionnaire was created, including the community of inquiry scale and the grit scale. A total of 529 valid and consented answers were collected. We have further analyzed the structure of the variables network with network analysis and then we have employed several sequential mediation analyses testing the impact of cognitive presence triggering events and resolution on the relationship between all the other presences and students’ academic perseverance. A circular structure has emerged in network analysis and eight significant full complementary sequential mediation analysis. Results confirm the domino effect of teacher cognitive presence triggering events and resolution on student’s grit under the community of inquiry framework.